A rapid and simple LC–MS/MS method for the simultaneous evaluation of CYP1A2, CYP2C9, CYP2C19, CYP2D6 and CYP3A4 hydroxylation capacity. (March 2014) - de Andrés, Fernando; Sosa-Macías, Martha; LLerena, Adrián
Background: The analytical method here reported for the CEIBA cocktail approach has been developed and validated for the simultaneous determination of several probe drugs and their corresponding cytochrome P450 (CYP) enzyme-specific metabolites in just one analysis. This methodology has been proposed in order to overcome some drawbacks concerning the complexity and low throughput of analytical methodologies associated with previously proposed cocktail approaches.Methods & results: Caffeine (CYP1A2), losartan (CYP2C9), omeprazole (CYP2C19), dextromethorphan (CYP2D6 and CYP3A4) and their corresponding metabolites were all analyzed in a single analytical run by gradient LC coupled to MS/MS. Sample preparation was conducted with solid-phase extraction. This method was fully validated and applied to CYP450 enzyme phenotyping of 20 healthy volunteers.Conclusion: This method constitutes a rapid and simplified analytical tool to be used with the CEIBA cocktail approach for the main CYP450 enzymes phenotyping.